Investigating polynomial approximations for the spectra of the pipe organ sound - KACZMAREK, A.; CZYŻEWSKI, A.; KOSTEK, B. (Archives of Acoustics, 1999)
An attempt was made to find some features describing the shape of the spectra of organ pipe sounds in terms of their subjective discernibility. A multi-channel recording system was employed in order to represent reliable pipe sounds in a realistic acoustic interior. A precise method for the determination of the spectral representation of pipe sounds was introduced. The polynomial approximation of the spectral envelope was found to be an effective tool, allowing the study of differences between sounds produced by organ pipes of various types belonging to some selected instruments. The paired comparison subjective testing procedure was applied in order to assess the similarities between sounds synthesized using polynomial smoothed spectra and the original organ sound patterns. The statistical processing of test results revealed that a direct relation exists between the type of organ pipe and the minimum order of the approximating polynomial that can be used to represent the pipe sound spectrum, as determined by the positive opinions of the experts. The applied pipe organ sound recording and processing methods, subjective testing procedures and experiment results are discussed in the paper.